(untitled) (Globalization and Business, 2023)
Tourism and hotel businesses are the sectors most affected by the COVID-19 pandemic in the Georgian economy.Despite the gradual removal of restrictions imposed during the pandemic period in early 2022, despite the transition to the tourismindustry recovery phase, it is important to assess the impact of the pandemic on the hotel sector to better identify post-pandemicchallenges and plan sustainable business development measures. The paper analyzes the impact of the global pandemic and other negative factors on the development of the hotel business inGeorgia, the main challenges, measures taken to mitigate the damage caused by the pandemic to the hotel sector, and the measurestaken to save the hotel business. The paper is based on a review of leading scientific publications and statistical data, an assessment of the main directions of thestate anti-crisis policy, government program 2021 - 2024 "Building a European state". Opinions are expressed on the mobilization of existing opportunities in the process of hotel business development in Georgiain the post-pandemic period and the emergence of new perspectives; in the new reality with the services traditionally consideredfor the hotel business, the introduction of innovative technologies and innovative products.